ALPHABET SUBSTITUTION OF DYSLEXIA STUDENTSAT YAYASAN PANTARA JAKARTA; A PSYCHOLINGUISTICS STUDY - Nurchaerani, Meiyanti; Imda, Asih Nur; Mardiani, Rini (Universitas Esa Unggul, 2018)
AbstractThis article is entitled Ã¢â‚¬Å“Substitution in Dyslexia Student of Yayasan Pantara Jakarta: A psycholinguistics StudyÃ¢â‚¬Â. The purpose of the study is to get more understanding about Substitution which is commonly experienced by several Dyslexic elementary school students between 8 to 10 years old who are studying in the 2nd to 4th grade of Sekolah Dasar Yayasan Pantara Jakarta, a very special school for those who experience Dyslexia, Dysgraphia, Dyscalculia and other special needs, which is located in Jalan Tebet Raya Jakarta Pusat. The main theory used for this study are taken from OÃ¢â‚¬â„¢Grady (1997) which particularly concerns about Psycholinguistics study, Gribben (2012) which mainly concerns about Dyslexia and Mc. Manis (1998) which focuses on Substitution. This is an experimental study with the students as the object of the research. Writing tests were explicated in this study. The writing test was concluded by practicing some words which are taken from LernerÃ¢â‚¬â„¢s theory about basic sight words which suitable for children in 2nd to 4th grade of elementary school students and also from SwadeshÃ¢â‚¬â„¢s 200 basic words which are already taught by their teacher while they are studying in their school. Meanwhile, the method used is descriptive-qualitative. The data is collected using qualitative method and furthermore is analyzed using descriptive method. This study brings out the finding that there is certain types of substitution commonly found among elementary school students in Yayasan Pantara Jakarta.Ã‚Â Keywords: psycholinguistics, dyslexia, substitutionÃ‚Â AbstrakArtikel ini berjudul Ã¢â‚¬Å“Sibstitusihurufpada Siswa Disleksia di Yayasan Pantara Jakarta: Studi PsikolinguistikÃ¢â‚¬Â. Tujuan dari penelitian ini adalah untuk mendapatkan pemahaman lebih lanjut tentang Substitusi yang umumnya dialami oleh beberapa siswa sekolah dasar disleksia antara 8 hingga 10 tahun yang belajar di kelas 2 hingga 4 Sekolah Dasar Yayasan Pantara Jakarta, sekolah yang sangat khusus bagi mereka yang mengalami Dyslexia, Dysgraphia, Dyscalculia dan kebutuhan khusus lainnya, yang terletak di Jalan Tebet Raya Jakarta Pusat. Teori utama yang digunakan untuk penelitian ini diambil dari O'Grady (1997) yang terutama membahas tentang studi Psikolinguistik, Gribben (2012) yang terutama membahas tentang Dyslexia dan Mc. Manis (1998) yang berfokus pada Substitusi. Ini merupakan penelitian eksperimental dengan siswa sebagai objek penelitian. Tes menulis dijelaskan dalam penelitian denganmelatih beberapa kata yang diambil dari teori Lerner tentang kata-kata dasar yang cocok untuk anak-anak di kelas 2 hingga 4 siswa sekolah dasar dan juga dari 200 kata dasar Swadesh yang sudah diajarkan oleh guru mereka saat mereka belajar di sekolah mereka. Sementara itu, metode yang digunakan adalah deskriptif-kualitatif. Data dikumpulkan menggunakan metode kualitatif dan selanjutnya dianalisis menggunakan metode deskriptif. Penelitian ini menghasilkan temuan bahwa ada beberapa jenis substitusi yang biasa ditemukan di kalangan siswa sekolahdasar di Yayasan Pantara Jakarta. Kata kunci: psikolinguistik, disleksia, substitusi